Insersi Pendidikan Antikorupsi Dalam Pembelajaran Shalat Perspektif Al Qur’an Dan Neurosains - Nugroho, Adi Bayu; Suyadi, Suyadi (Civiliza Publishing, Indonesia., 2024)
Corruption is a big problem in Indonesia which is still deeply rooted today. Seeing this problem, of course the world of education now seems to feel responsible for the importance of awareness against corruption. Insertion of anti-corruption education can be carried out in many learning materials, one of which is Islamic Religious Education, which in this research focuses on learning prayer. In the Al-Qur'an, Surah Al-Ankabut verse 45, it is stated that prayer can prevent evil and evil acts. In a hadith, the Prophet said that people who do not complete bowing and prostration in prayer are like thieves. Prayer is a self-control system from the perspective of the Koran. From a neuroscientific perspective, prayer is an important aspect in optimizing the emotional brain and spiritual brain. So optimizing prayer learning is very important as an effort to insert anti-corruption education into Islamic religious education. This research aims to see the extent of the role of prayer in preventing corruption. And what steps are being taken in efforts to insert anti-corruption education into Islamic Religious Education. This research is included in the library research category using literature as a data source. Data analysis by examining various documents in the form of research journals or books related to research data using qualitative research data analysis techniques. The results of this research understand that one of the causes of problems in this country is the lack of optimal prayer learning in Islamic Religious Education. Prayer is a self-control system from the perspective of the Qur'an and has an influence on optimizing the emotional and spiritual brain. By understanding the importance of prayer and teaching it optimally, it is hoped that it will give birth to a generation that is far from corruption.